Volumetric MRI Analysis of a Case of Severe Ventriculomegaly - Alders, Gésine L.; Minuzzi, Luciano; Sarin, Sachin; Frey, Benicio N.; Hall, Geoffrey B.; Samaan, Zainab (Frontiers in Human Neuroscience, 2018)
We present a case of a 60-year-old male referred to a tertiary psychiatric facility for diagnostic assessment due to low mood and behavioural changes. Neurological examination of the patient was unremarkable. MRI indicated overt ventriculomegaly with gross dilatation of lateral and third ventricles. Manual segmentation of grey matter, white matter, and CSF demonstrated that the patient had a ventricular volume almost 46 times greater than that of healthy volunteers in the same age range. Despite his striking degree of ventriculomegaly and cortical thinning, he presented primarily with psychiatric and cognitive complaints. These represented a major neurocognitive disorder. His behavior improved with a structured environment and routine instituted by the treating team. This is a dramatic example of the brain’s response to extreme structural remodeling. Elements of pluripotentiality may counteract degeneracy to preserve functions in cases of serious structural stress in the brain. Changes in the neural circuitry of emotional processing, and/or disruption in signaling pathways important for synaptogenesis may influence depression pathophysiology. How this circuitry is modified in cases of extreme structural stress such as longstanding overt ventriculomegaly, is unclear. This case demonstrates the ability of the brain to generate a normal phenotype despite structural changes that seem incompatible with advanced cognitive function, illustrating the substantial potential for adaptability and plasticity in the brain.